Complement Inhibitor Therapy for Myasthenia Gravis - Albazli, Khaled; Kaminski, Henry J.; Howard, James F. (Frontiers in Immunology, 2020)
Complement activation as a driver of pathology in myasthenia gravis has been appreciated for decades. The terminal complement component (membrane attack complex) is found at the neuromuscular junctions of patients with myasthenia gravis. Animals with experimental autoimmune myasthenia gravis are dependent on an active complement system to develop weakness. Mice deficient in intrinsic complement regulatory proteins demonstrate a significant increase in the destruction of the neuromuscular junction. As subtypes of myasthenia gravis have been better defined, it has been appreciated that acetylcholine receptor antibody-positive disease is driven by complement activation. Preclinical assessment confirmed that complement inhibition would be a viable therapeutic and recently eculizumab, an antibody directed towards the C5 component of complement, was demonstrated to be effective in a Phase 3 trial with subsequent approval by the Federal Drug Administration of the United States and other world-wide regulatory agencies for its use for acetylcholine receptor antibody-positive myasthenia gravis. Second and third generation complement inhibitors are in development and approaching pivotal efficacy evaluations. This review will summarize the history and present state of knowledge of these new therapeutic agents.